(3efgGL GdhUhd Edi Yde GdCUhds - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3JbOS ef JeLO HGdYXeI hGdLdGd hHYO aEf Chdi eG Jge Hg Gdgee GdYhGdi JYde GdeYGde GdOjfjI hEf cJGHfG gPG efgGL GdhUhd Edi Yde GdCUhd GdLGeY Hjf GdeTQhY hGdeYbhd GdHGH GdChd ai GdMce s
(3BNQgG (B:s
(3GdKGdKI EfeG jLhR ai GdaQhY hbO ENJda ai GdCUhd hdfG ajg fXQ hdjcf gPG BNQ cdGefG hGdgd Gdehab hGdgGOi deG jNJGQ hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG ebGHdI hbQGAI Ydi GdTjN LeGd GdOjf YHO GdQMje Hf GdMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs